Respuesta :
Take out a common factor between 3x and kx. That means use the distributive law to get what you normally would start with.
x(k + 3) = 4
Now divide by k + 3
x = 4/(k + 3)
That's as much as you can do with this question.
The given algebraic expression is made up of a constant(x) and a variable.
Given that:
kx + 3x = 4
the first thing to do is to identify the common like terms.
Here, kx and 3x are the two common terms.
Let's factorize out x from the two terms, by doing so, we have:
x(k + 3) = 4
The next thing to do is to divide both sides by (k +3) since we are solving for x.
[tex]\mathbf{\dfrac{x(k+3)}{(k+3)}= \dfrac{4}{(k+3)}}[/tex]
[tex]\mathbf{x= \dfrac{4}{(k+3)}}[/tex]
Therefore, we can conclude that the solution for (x) to the simplest term is:
[tex]\mathbf{ \dfrac{4}{(k+3)}}[/tex]
Learn more about algebraic expression here:
https://brainly.com/question/953809?referrer=searchResults